Mergers and Stock Market Reaction: Evidence from India - Debi Prasad Satapathy, Sameer Shekhar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The paper tries to search is there any relationship between mergers of acquiringevents and corporate market performance.Mergers and acquisitions have been used by corporate to create value for shareholders through expansion and consolidation. There are extensive studies documented abroad about value creation to shareholders through mergers and acquisitions. The literature on mergers indicates there is a mixed view regarding wealth creation to shareholders both in market-based as well as accounting-based studies. There is a dearth of studies in the Indian context whether mergers create value to shareholders or not. This motivates me to explore whether there is any relationship between creating wealth for shareholders in the short run by using the market-based measure. The objective of this study to explore do acquire firms generate an abnormal return to the shareholders in the Indian context upon merger announcement. The paper tries to examine whether any positive return generated by a firm because of mergers and acquisitions announcedin the short run by using event study methodology. The studyhas takena sample of 371 acquiring for the period from 2008-2013 to analyze the effect of the merger on shareholder wealth by using listed companies in the Indian perspective. The results were found to be a positive abnormal return to the shareholders of the acquiring firm’s window period of [-20, 20]forIndian acquiringcompanies.